Assessment of pesticide application quality with a manual sprayer in spinach (2016)
Two experiments were conducted to evaluate the performance of three hollow cone nozzles (TeeJet® TX 800050 VK, TeeJet® TXA 8004 VK and TX-Royal Condor®) and one flat fan nozzle (TeeJet® XR 8004 VS) with two manual application techniques on a crop of spinach (Spinacia oleracea L.). In order to assess the quality of the application of pesticides, WSP (water sensitive paper) collectors and fluorescent tracer Tinopal® CBS-X were used. In one of the trials, percentage of tracer retained by the leaf surfaces was also determined. In this study, and based on the methodology of collectors, it was observed that the technique of applying two passes with the TX-Royal Condor® nozzle could be recommended for the application of pesticides with a hand-operated sprayer in the spinach crop. However, this was not corroborated by the fluorescent tracer technique.